Byzantinische Epigramme in inschriftlicher Überlieferung. Band 3, Teil I Byzantinische Epigramme auf Stein nebst Addenda zu den Bänden 1 und 2 - Rhoby, Andreas (Verlag der Österreichischen Akademie der Wissenschaften, 2014)
In Byzantium the epigram as a genre was highly appreciated. Their analysis is the aim of the four planned volumes of the project "Byzantinische Epigramme in inschriftlicher Überlieferung" ["Byzantine epigrams on objects"]. More than 300 and such epigrams preserved on stone, which are treated in the present third volume, are known from the project period 600 AD to 1500 AD.